Simultaneous treatment of agro-food and asbestos-cement waste by the combination of dark fermentation and hydrothermal processes. (October 2019) - Race, Marco; Spasiano, Danilo; Luongo, Vincenzo; Petrella, Andrea; Fiore, Saverio; Pirozzi, Francesco; Fratino, Umberto; Piccinni, Alberto F.
Abstract: The inadequate management of asbestos-cement products (ACP) and/or wastes (ACW) generates hazardous airborne dusts. For this reason, the EU is promoting the removal of ACP from utilities, public and private buildings and is looking for innovative ACW treatments alternative to the landfilling. The simultaneous treatment of ACW and orange pulp or cheese whey was attempted with a mesophilic dark fermentation (DF) process followed by a 12 h hydrothermal (HT) treatment carried out with the addition of lactic or oxalic acid at 100 °C and ambient pressure. The DF of orange pulp or cheese whey in the presence of 5 g L −1 ACW lasted 171 h and led to the production of 4 L H 2 and 5 L H 2 per litre of solution, respectively. During the DF, the dissolution of the ACW matrix was almost completed, and the partial collapse of the asbestos fibres was observed. Both the organic acids that were added during the HT tests at a concentration ≥2.5 g L −1 completely destroyed the asbestos fibres. However, when 1.25 g L −1 lactic or oxalic acid was added before the HT tests, few fibre fragments were found, and their chemical composition differed from that of chrysotile. Graphical abstract: Image 1 Highlights: An Eternit sample was treated by dark fermentation and hydrothermal processes. Orange pulp and cheese whey were used as substrates during dark fermentation. Due to the presence of limonene, orange pulp led to a lower H2 production. In both cases, dark fermentation led to a partial destruction of chrysotile fibres. Hydrothermal treatments (100 °C) lasting 12 h completed the asbestos destruction.